2012
DOI: 10.1089/ten.tea.2011.0411
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Bone Colonization and Aggregate Culture Conditions Diversely Influence Murine Periosteum Mesenchymal Stem Cell Differentiation Potential in Long-TermIn VitroOsteoinductive Conditions

Abstract: Periosteum contains mesenchymal stem cells (Pe-MSCs) that contribute to normal bone growth, healing, and turnover; understanding Pe-MSC capabilities may shed light over the treatment of bone defects using tissue engineering. Bone tissue regeneration needs in vitro bone precursors or stem cell coculture onto specific scaffolds but, despite extensive research in the field, very little is known about the matrix structure of the tissue-engineered tissues and the scaffold's effects on cell differentiation. To this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…33 Like bone marrow-derived MSCs, the differentiation of PDCs can also be profoundly impacted by the scaffold environment that they adhere to, underscoring the importance of choosing a suitable biomaterial scaffold for the delivery of exogenous PDCs to promote bone healing. 34 In this study, we demonstrate the advantages of rat PDCs over bone marrow-derived MSCs in terms of their in vitro proliferation and osteogenic differentiation potential. Further, we compare the efficacy of an uncharged electrospun cellulose fibrous mesh and a negatively charged sulfated electrospun fibrous mesh recently developed in our laboratory 35 in supporting the cellular attachment, proliferation and osteogenic differentiation of PDCs.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…33 Like bone marrow-derived MSCs, the differentiation of PDCs can also be profoundly impacted by the scaffold environment that they adhere to, underscoring the importance of choosing a suitable biomaterial scaffold for the delivery of exogenous PDCs to promote bone healing. 34 In this study, we demonstrate the advantages of rat PDCs over bone marrow-derived MSCs in terms of their in vitro proliferation and osteogenic differentiation potential. Further, we compare the efficacy of an uncharged electrospun cellulose fibrous mesh and a negatively charged sulfated electrospun fibrous mesh recently developed in our laboratory 35 in supporting the cellular attachment, proliferation and osteogenic differentiation of PDCs.…”
Section: Introductionmentioning
confidence: 65%
“…due to less calcium ions attracted to the uncharged mesh) by up-regulating the gene expression of osteocalcin, a protein known to regulate/template mineralization. 44 It was previously reported that the expression of osteogenic markers by PDCs upon osteogenic induction does not always correlate with the extent of mineral depositions, 34 and that similar osteocalcin expression by MSCs and PDCs in response to osteogenic induction does not necessarily translate into similar levels of mineral deposition. 45 Cautions should be exercised in assessing osteogenesis outcome.…”
Section: Resultsmentioning
confidence: 99%
“…MSCs are multipotent cells derived from bone marrow that have the ability to differentiate into cells of mesenchymal and nonmesenchymal origin [ 22 ], such as osteocytes [ 23 ], chondrocytic, adipocytes [ 24 , 25 ] and myocytes [ 26 ]. Moreover, MSCs appear to function through paracrine mechanisms that exert immunosuppressive, anti-inflammatory, anti-apoptotic and other organ-protective and repair-stimulating actions [ 22 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%